2021
DOI: 10.3390/ijms222413316
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in the Involvement of the Endocannabinoid System and Natural Cannabinoids in Nicotine Dependence

Abstract: Nicotine, the main psychoactive component in tobacco smoke, plays a major role in tobacco addiction, producing a high morbidity and mortality in the world. A great amount of research has been developed to elucidate the neural pathways and neurotransmitter systems involved in such a complex addictive behavior. The endocannabinoid system, which has been reported to participate in the addictive properties of most of the prototypical drugs of abuse, is also implicated in nicotine dependence. This review summarizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 181 publications
(234 reference statements)
2
3
0
Order By: Relevance
“…26 Upregulation of CB1R in these regions is associated with the development of nicotine and cocaine addiction. 27,28 In the present study, we confirmed that oxycodone could evaluate the expression of CB1R in the hippocampus (Figure 3A), suggesting that the dysregulation of the ECS is also linked to oxycodone abuse. During the development of synapse, CB1R can mediate the activation of Cdk5 and cause neurobehavioral abnormalities in mice postnatally exposed to alcohol.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…26 Upregulation of CB1R in these regions is associated with the development of nicotine and cocaine addiction. 27,28 In the present study, we confirmed that oxycodone could evaluate the expression of CB1R in the hippocampus (Figure 3A), suggesting that the dysregulation of the ECS is also linked to oxycodone abuse. During the development of synapse, CB1R can mediate the activation of Cdk5 and cause neurobehavioral abnormalities in mice postnatally exposed to alcohol.…”
Section: Discussionsupporting
confidence: 81%
“…Regions of highest expression include the basal ganglia, cerebellum, olfactory bulb and hippocampus 26 . Upregulation of CB1R in these regions is associated with the development of nicotine and cocaine addiction 27,28 . In the present study, we confirmed that oxycodone could evaluate the expression of CB1R in the hippocampus (Figure 3A), suggesting that the dysregulation of the ECS is also linked to oxycodone abuse.…”
Section: Discussionsupporting
confidence: 79%
“…Although it was not surprising that rimonabant reduced the subjective effects of cannabis, evidence that this medication also reduces the reinforcing effects of nicotine was one of many clues that targeting the eCB may have potential to treat a range of SUDs. To start preclinically, CB1R antagonists reduce nicotine reinforcement [see (Saravia, Ten-Blanco, Pereda-Pérez, & Berrendero, 2021 ; Spanagel, 2020 )], presumably by blocking eCBs from disinhibiting dopaminergic neurons in the ventral tegmental area [see (Asth, Santos, & Moreira, 2022 ; Butler & Le Foll, 2020 )]. These findings appear consistent with human imaging data [summarized by (Hirvonen et al, 2018 )] – with cannabis, THC acts on CB1Rs directly and thereby downregulates CB1Rs in neocortical brain regions but not in the basal ganglia, midbrain, or cerebellum.…”
Section: Substance Use Disordersmentioning
confidence: 99%
“…Regarding AEA and 2-AG, studies have provided conflicting results about their reinforcing properties for nicotine and nicotine withdrawal. However, AEA and 2-AG could have opposite roles in relapse to nicotine-seeking behavior [421].…”
Section: Animal Studiesmentioning
confidence: 99%